GANGGUAN PERSEPSI SENSORI SEBAGAI DASAR PERANCANGAN PANTI REHABILITASI ANAK AUTIS DI SURAKARTA - Ganis Ratna Satyawati; Edi Pramono Singgih; Ofita Purwani (Universitas Sebelas Maret Surakarta, 2017)
Autism is one delay in child development. It is the result of complex and varied brain development disorders, one of them is disturbance in sensory system (sensory integration) in children. The disturbance causes the children to be unable to adapt optimally, thus, it affects behavioral and psychological responses of children with autism in their environment. The number of children with autism increases from year to year, including in Surakarta. A rehabilitation centre is therefore needed in this city. This rehabilitation centre for children with autism is uses a functional recovery for behavior, occupation, and nervous system (neurons), and sensory systems of children who experienced the disorder to regenerate its form or function. This rehabilitation centre will accommodate medical, therapeutic, and educational activities by using special environmental designs planned according to the sensory needs and specific stimuli needs for each different autistic child. The design concept of this rehabilitation centre focuses on the sensory needs of children with aurism. It will be applied through building physical elements in the form of inside and outside spatial elements. Both elements will be designed with various considerations of the choice of attributes or architectural elements, such as: design principles, shapes, scales, colors, building materials. These considerations will create specific effects for each individual with different levels of sensory perception disorder. This rehabilitation favility will provide 5 special zones for autistic children which are categorized based on the level of disturbance and condition of the children. The categorization is expected to play a major role in accelerating the process of healing and development of children physically, psychologically, intellectually, and socially. Consequently, it can establish a child with autism into an independent, creative, exist, and skilled human as other normal children.